Carotene and provitamin A content of vegetables sold in Viçosa, MG, Brazil, during spring and winter - Pollyanna Costa Cardoso; Ceres Mattos Della Lucia; Paulo César Stringheta; José Benício Paes Chaves; Helena Maria Pinheiro-Sant'Ana (Universidade de São Paulo, 2009)
This study investigated the α- and β-carotene content and provitamin A value of four leafy vegetables sold at local and street markets in Viçosa, MG, Brazil, in the spring and winter of 2002. Carotenoids were analyzed by high-performance liquid chromatography. α-Carotene was detected in all samples sold during spring, but was only present in a few samples of smooth and curly lettuce and kale in winter. β-Carotene was found in marked quantities in all leafy vegetables analyzed. Duncan's test (α = 5%) showed significantly higher α-carotene content in curly lettuce and vitamin A value in large-leaved watercress in the spring. Mean β-carotene content and vitamin A value were 7544, 8751, 2584, 2792, 8193, and 5338 μg/100 g and 666, 760, 227, 238, 698, and 460 μg RAE/100 g in large-leaved and hydroponic watercress, smooth and curly lettuce, kale and spinach, respectively. All leafy vegetables analyzed represent important sources of provitamin A and supply an important part of the daily requirements of children and adults. Investigou-se o conteúdo de α e β-caroteno e avaliou-se o valor pro-vitamínico A de quatro hortaliças folhosas comercializadas em mercados locais e feira- livre de Viçosa, MG durante a primavera e o inverno de 2002. Os carotenóides foram analisados por Cromatografia Líquida de Alta Eficiência (CLAE). O α-caroteno foi detectado em todas as amostras analisadas na primavera, porém no inverno, somente algumas amostras de alface crespa e lisa, e couve apresentaram tal carotenóide. O β-caroteno foi encontrado, em quantidades apreciáveis, em todas as hortaliças folhosas analisadas. O teste de Duncan (α=5%) detectou que o conteúdo de α-caroteno em alface crespa e o valor de vitamina A em agrião de folha larga foram estatisticamente superiores na primavera. Os teores médios de β-caroteno e de valor de vitamina A para agrião de folha larga e hidropônico, alface crespa e lisa, couve e espinafre foram: 7544; 8751; 2584; 2792; 8193; 5338 μg/100g e 666; 760; 227; 238; 698; 460 μg RAE/100g, respectivamente. Todas as hortaliças folhosas analisadas constituem importantes fontes de provitamina A e suprem grande parte das recomendações diárias de crianças e adultos.